Double‐blind randomized phase III study comparing a mixture of natural agents versus placebo in the prevention of acute mucositis during chemoradiotherapy for head and neck cancer. Issue 9 (31st May 2017) - Marucci, Laura; Farneti, Alessia; Di Ridolfi, Paolo; Pinnaro, Paola; Pellini, Raul; Giannarelli, Diana; Vici, Patrizia; Conte, Mario; Landoni, Valeria; Sanguineti, Giuseppe
Abstract: Background: There is no widely accepted intervention in the prevention of acute mucositis during chemoradiotherapy for head and neck carcinoma. In the present double‐blind study, we tested 4 natural agents, propolis, aloe vera, calendula, and chamomile versus placebo. Methods: Patients undergoing concomitant chemo‐intensity‐modulated radiotherapy (IMRT) were given natural agent or matched placebo; grade 3 mucositis on physical examination according to Common Terminology Criteria for Adverse Events (CTCAE) version 3.0 was the primary endpoint. Various covariates were tested at logistic regression, including the individual amount of mucosa receiving at least 9.5 Gy per week (V9.5w). Results: One hundred seven patients were randomized from January 2011 to July 2014, and 104 were assessable (51%‐49% were assigned to the placebo group and 53%‐51% were assigned to the natural agent). Overall, 61 patients developed peak grade 3 mucositis with no difference between arms ( P  = .65). Conversely, V9.5w ( P  = .007) and primary site ( P  = .037) were independent predictors. Conclusion: The selected natural agents do not prevent mucositis, whereas the role of V9.5w is confirmed.